Воспитательно–познавательный аспект поэтического наследия У. Сами - Меметова, Л.А. (Культура народов Причерноморья, 2013)
В статье представлены отдельные образцы поэтического наследия У. С. Арбатлы,
вошедшие в изданные им для школ рушдие (средняя школа) в 1910 и 1914 гг. книги для чтения
«Чоджукълара аркъадаш» («Друг детей»). В результате проведенного художественного анализа
произведений определена тематическая направленность и поэтические особенности лирики У. С.
Арбатлы. Поэзия педагога У. Сами, не смотря на то, что она представлена считанным количеством
произведений, является одной из основополагающих принципов воспитания молодого поколения первой
половины XX века, интересной и малоизученной страницей крымскотатарской литературы периода
Возрождения. У статті представлені окремі зразки поетичної спадщини У. С. Арбатли, що увійшли до
видані ним для шкіл рушдіє (середня школа) в 1910 і 1914 рр. книги для читання «Чоджуклара Аркадаш»
(«Друг дітей»). У результаті проведеного художнього аналізу творів визначена тематична
спрямованість і поетичні особливості лірики У. С. Арбатли. Поезія педагога У. Самі, не дивлячись на
те, що вона представлена невеликою кількістю творів, є однією з основоположних принципів виховання
молодого покоління першої половини XX століття, цікавою і маловивченою сторінкою
кримськотатарської літератури періоду Відродження. The reason for writing this article was the desire to enter into scientific use facts from little–known
sources associated with the work of the Crimean Tatar poet and teacher of the early XX century Umer Arbatly
Sami. The article provides a brief autobiographical information about the poet and some samples of his poetic
heritage included the books to read "Chodzhuklara arkadash" ("Friend of Children") which he published for
Rushdie school (high school) in 1910 and 1914. As a result of the artictic analysis of his works, is defined
thematic focus and poetic features of the lyrics of U.S. Arbatly. Educational aspect of his work is reflected in the
pages of studied textbooks, enables to believe his high pedagogical skills, teaching the students through the
grace of the poetic word. Landscape motifs dominates his lyrical heritage, promote the development of students'
knowledge about the environment and building respect for nature. Although, there are known a few works of the
teacher U. Sami in the world, his poetry is one of the fundamental principles of education of the younger
generation of the Crimean Tatars first half of the XX century. In addition, his works is amazing and little–studied
page of the Crimean Tatar Renaissance literature.